Parental hypoxic exposure influences performance of offspring in Callosobruchus maculatus. Issue 10 (1st April 2019) - Sang, Wen; Ji, Rui; Lei, Chaoliang; Zhu‐Salzman, Keyan
Abstract: Background: Modified atmosphere based on lack of O2 can protect stored grains from insect pest damage. Although population expansion of cowpea bruchid ( Callosobruchus maculatus (Fabricius)) could be temporarily arrested when exposed to 2% O2, this insect could survive extended periods of hypoxia and continue its normal development if normoxic conditions resumed. It is not clear whether parental hypoxic treatment has any effects on offspring performance and response to hypoxia. Results: Hypoxia postponed development of treated parental bruchids at all stages. Its negative effects on oviposition and hatch rate of these eggs were significant only when hypoxia was administered at the parental fourth instar larval stage or later. When the F1 generation was exposed to hypoxia at the fourth instar larval stage, they exhibited comparable developmental delay and reduction in adult emergence and fecundity whether the parents experienced hypoxia or not. Interestingly, eggs laid by hypoxia‐treated F1s had increased hatch rates if their parents had also been exposed to hypoxia. Stronger suppression of the digestive protease gene CatL and elevated basal expression of the stress responsive gene Hsp27 were observed in F1 larvae with parental hypoxic experience. Conclusion: Parental hypoxic experience appeared to better prepare the F1 progenies for further hypoxic challenge. © 2019 Society of Chemical Industry Abstract : Parental hypoxic exposure influenced the performance of both parental and F1 generations of cowpea bruchids, and prepared F1 progenies to better handle future hypoxic challenge.